Catalytic co-pyrolysis of tetra-pax and low-density polyethylene (LDPE) waste mixtures using calcium oxide catalyst via artificial neural network approach: synergistic interactions, kinetic and thermodynamic analyses - Sharon Goh, Meng Xuang; Bridgid Chin, Lai Fui; Tan, Yie Hua; Zeinab Abbas, Jawad; Dana H., Abdeen; Lam, Man Kee; Chai, Yee Ho; Serene Lock, Sow Mun; Yiin, Chung Loong; Adrian Loy, Chun Minh (Springer Nature, 2025)
In this study, mixture of tetra-pak carton and low-density polyethylene (LDPE) was investigated by using thermogravimetric analysis under various heating rates, 10–100 °C min−1 from temperature 50 °C to 900 °C with the presence of calcium oxide (CaO) catalyst. The synergistic interaction between tetra-pak carton and LDPE was also observed. Aside from that, artificial neural network (ANN) was employed to predict the experimental data. It is found that ANN is able to predict the experimental data with high accuracy. Kissinger–Akahira–Sunose (KAS), Friedman (FR) and Starink models were used to determine the kinetic parameters (activation energy, Ea and pre-exponential factor, A). With the presence of catalyst, the Ea of the mixture successfully decreased from 212.15–220.40 kJ mol−1 to 190.71–202.35 kJ mol−1, resulting in an approximate reduction of 3.9–6.1%. Furthermore, positive enthalpy (ΔH) and Gibbs free energy (ΔG) indicate the reaction in this study is endothermic and non-spontaneous behaviour. Meanwhile, the change of entropy (ΔS) value obtained in this study is < 0.5 kJ mol−1 K−1, implying that solid substances have undergone physical and chemical reactions that brought it nearer to its thermodynamic equilibrium state. The generated results in this study would greatly aid in scaling up the design of a pyrolysis reactor by using these feedstocks in the future.